Lacan’s Last Mistakes: The Non-Existence of the Sexual Relation and the Woman as Exception. A Logical and Philosophical Inquiry (ENTHYMEMA, 2025)
Two theses have made Lacan’s Seminar XX famous: the non-existence/impossibility of the sexual relation (‘il n’y a pas de rapport sexuel’) and the non-existence of ‘THE Woman.’ Conceptually speaking, then, it is negation that must be recognized as the true protagonist of this Seminar. Yet negation is a polysemic logical connective, and Lacanian scholasticism tends to ignore this. The ‘not’ of the sexual relation is now cited as a self-evident truth: its paradoxical nature has been almost entirely lost, and ‘il n’y a pas de rapport sexuel’ ends up sounding very much like ‘Santa Claus does not exist.’ The first and foremost culprit of this inevitable degradation is Lacan himself, for two reasons: first, because his arguments, if examined carefully, appear inconsistent and verge on the ridiculous; and more importantly, because they are based on the fallacy that ‘THE Logic’ exists. Lacan’s major error was to believe that the logic of Frege and Russell was the only possible one. In reality, it corresponds to a separative style of thought, which produces distortions and falsehoods when applied to conjunctive and flexible relationships – relationships that human beings cannot renounce. There is another meaning of negation: an overcoming ‘not’, endowed with a force of nihilation – the very force that femininity (once freed from the mantra of alterity) reveals in its power, so closely akin to that of psychoanalysis.
Keywords: Jacques Lacan; Seminar XX; Sexual Relation; Femininity; Nihilation